The Current Scenario of Clinical Pharmacy Service in the Management of Patients with Diabetes Mellitus and Related Complications: Review Article - Demoz, Gebre Teklemariam; Gebremariam, Gebremichael; Legesse, Yirga (Indian Journal of Pharmacy Practice)
Diabetes Mellitus (DM) is a group of metabolic disorder characterized by defect in insulin secretion, insulin action or both. The prevalence of diabetes continues to rise worldwide, placed in an increasing burden on healthcare systems and for the individual payers. This review is aimed to organize and examines the contribution of pharmacist in people living with diabetes mellitus and reviewed to whether the extent of diabetes management interventions delivered by pharmacist is successful in achieving the goal of therapy in DM patients. Many studies revealed and confirmed that the positive impacts of pharmacists intervention on monitoring of blood glucose level, blood pressure, lipid profiles, body mass indexes, diabetes related complications, economic benefits, improving health related quality of life, drug-related problems, adherence to medication, provision of patient education and counseling services, medication therapy management services and other pharmaceutical care services that enhance the clinical outcomes in diabetes patients were better than the usual care services. In all cases, it was proven that the intervention was successful in achieving the goals of therapy in diabetes patients and reducing other complications associated with the disease. Therefore, pharmacist integration into a health care team had shown to be effective in improving a number of clinical health outcomes in diabetic patients. This may be helpful to realize the current progress of pharmacist’srole in people living with diabetes and associated complications.
Keywords: Diabetes mellitus; Pharmaceutical care; clinical pharmacist service